Covid-19 (in) a Class of Its Own: Student and Teacher Musings Regarding Their Learnings and Well-Being when Moving a Large Blended First Year Class Virtually Overnight - Trafford, Julie; Haxell, Ailsa; Lau, Kelvin; Carlson, Gema; Rebelo da Silva, Ana Patricia; Hart, Andrew; De Freitas, Thais Regina; Rope, Sheridan (Frontiers in Education, 2021)
Covid-19 is (in) a class of its own in its influence on human lives and livelihoods globally, precipitating steep learning and psychological well-being curves for university teachers and students. This has impacted dramatically on the conditions under which higher education has had to function in regard to research and what is now referred to as ‘emergency online education’. As staff face unprecedented challenges, so too do students. Given that the consequences of these times are likely to be felt well into the future, it is important to capture what is happening now. We therefore present this perspective piece comprising 13 musings co-authored by students and educators regarding our experiences of two lockdowns within Aotearoa New Zealand in 2020 representative of the disrupted university in its adjustment to learning and teaching. In contributing to calls to develop a post-pandemic pedagogy for higher education, and better support staff and student well-being, we draw on methods that would multiply questions and invoke possibilities, as an impetus for reimagining higher education. Making use of a cogenerative dialoguing process, these musings enable multiple voices to be heard and considered. A non-representational lens enables us to explore the what and how of Covid-19 creating disruption and uncertainty for students’ and educators, influencing their psychological well-being and higher education pedagogy and practices, and becoming a contextually relevant taonga (treasure) of experiences that might inform future educational activities.